2018
DOI: 10.1210/jc.2018-00923
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Renal Function and Calcifications in Primary Hyperparathyroidism: A Nested Case-Control Study

Abstract: Renal calcifications are frequent in patients with PHPT and are associated with the severity of the disease. Impaired renal function is also common in PHPT, but renal function was not associated with renal calcifications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 44 publications
5
32
0
Order By: Relevance
“…8 Interestingly, predictors of renal dysfunction described by Walker et al 8 (namely age and hypertension) were not found to be associated with urinary KIM-1 excretion in our cohort. In accordance with recent data by Ejlsmark-Svensson et al, 7 factors related with severity of the disease were instead associated with the urine KIM-1/uCr ratio. Notwithstanding the differences in the populations studied, these findings seem to indicate that urine KIM-1/uCr ratio could be considered not only a sensitive but also a specific marker of renal damage during PHPT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…8 Interestingly, predictors of renal dysfunction described by Walker et al 8 (namely age and hypertension) were not found to be associated with urinary KIM-1 excretion in our cohort. In accordance with recent data by Ejlsmark-Svensson et al, 7 factors related with severity of the disease were instead associated with the urine KIM-1/uCr ratio. Notwithstanding the differences in the populations studied, these findings seem to indicate that urine KIM-1/uCr ratio could be considered not only a sensitive but also a specific marker of renal damage during PHPT.…”
Section: Discussionmentioning
confidence: 99%
“…With reference to the renal involvement, patients with PHPT may present nephrolithiasis (the most common complication of the disease), nephrocalcinosis, hypercalciuria and chronic kidney disease (CKD) . In particular, an estimated glomerular filtration rate (GFR) <60 mL/min is reported in a figure of 12%‐19% depending on series and this value represents the threshold under whom parathyroidectomy is recommended . The pathophysiology of CKD in PHPT is not completely understood.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the recent Danish study, the overall prevalence of vertebral fractures was around 22% for all age groups, and of interest higher in men compared with women in younger patients less than 60 years. Most of the fractures were mild to moderate and only 28.7% had severe fractures by the method of Genant (111, 112). When compared to patients with postmenopausal osteoporosis, patients with PHPT seemed to fracture at a higher BMD level (112).…”
Section: Primary Hyperparathyroidismmentioning
confidence: 99%